Fox on the run – molecular surveillance of fox blood and tissue for the occurrence of tick-borne pathogens in Austria - Duscher, Georg Gerhard (Parasit Vectors, 2014)
BACKGROUND: The red fox (Vulpes vulpes) is a widespread species, harbouring many pathogens relevant for humans and pets. Indeed, Anaplasma spp., Ehrlichia canis and Rickettsia spp. among the bacteria and Hepatozoon canis as well as Babesia sp. among the parasites have been the focus of several studies. FINDINGS: In a cohort of 36 foxes shot on one day in the north-eastern part of Austria, Babesia microti-like pathogens were found in 50%, while H. canis was detected in 58.3% of the samples. The spleen was more useful for detection of H. canis, whereas B. microti-like parasites were more frequently found in the blood. Bacteria could not be confirmed in any of the cases to demonstrate the occurrence of such tick-borne pathogens using PCR and sequencing on blood and spleen samples. CONCLUSIONS: The occurrence of B. microti-like and H. canis parasites raised many questions, because these infections have never been found autochthonously in dogs. Furthermore in the case of H. canis the main vector tick, Rhipicephalus sanguineus, is absent in the sampling area, leaving space for further hypotheses for transmission such as vertical transmission, transmission via ingestion of prey animals or other vector ticks. Further studies are needed to evaluate the risks for pets in this area. PCRs delivered differing results with the different tissues, suggesting the use of both spleen and blood to obtain an integral result.